Dampak Hard Skill dan Soft Skill terhadap Kesiapan Kerja dengan Motivasi Kerja sebagai Variabel Intervening pada Mahasiswa Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Dian Nuswantoro yang Mengikuti Program Magang - Putri Ernita Rahmawati; Artha Febriana; Raden Ayu Aminah Rizkia Puspita Sari; Masitha Fahmi Wardhani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
In order to examine how work motivation mediates the link between hard skills, soft skills, and work preparedness, this study focuses on seventh-semester management students who completed internships at Dian Nuswantoro University during the 2025-2026 academic year. The purpose of the research is to look at how different types of abilities, both hard and soft, affect job readiness and motivation. Partial Least Squares Structural Equation Modeling (PLS-SEM) and SmartPLS 4 were used for statistical analysis of the survey data. Students in their seventh semester of management programs who had completed internships were selected using a purposive sample technique. The results demonstrate that students' employment readiness is positively and significantly affected by their job motivation, which is affected by both their hard and soft skills. Mediation studies have shown that intrinsic job motivation strengthens the relationship between job readiness, hard skills, and soft skills. The R² value for work readiness is 0.751, which means that Hard Skills, Soft Skills, and Work Motivation together explain 75.1% of the variation. In contrast, the R² value for work motivation is 0.685, which suggests that Hard Skills and Soft Skills account for 68.5% of the variation. This study's findings highlight the importance of internships in enhancing management students' job motivation, technical competence, and interpersonal skills in order to better prepare them for the profession upon graduation. This study presents strong evidence that schools should focus on helping students improve their hard skills, soft skills, and motivation for the job as important strategies for preparing them for the workforce.